The Development of a Scarcity Bias. Issue 5 (5th April 2020) - Ferera, Matar; Benozio, Avi; Diesendruck, Gil
Abstract : Adults' attraction to rare objects has been variously attributed to fundamental biases related to resource availability, self‐related needs, or beliefs about social and market forces. The current three studies investigated the scarcity bias in 11‐ and 14‐month‐old infants, and 3‐ to 6‐year‐old children ( N = 129). With slight methodological modifications, participants had to choose between one of 10 same‐kind‐items (abundant resource), or the only one of a different kind (scarce resource). It was found that a robust preference for the scarce resource appeared only at age 5 years. Thus, although a scarcity bias is not present in infancy, it emerges prior to comprehension of market forces. Possible accounts of this developmental finding are discussed.